2019
DOI: 10.1002/hep.30274
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Risk Score in Predicting Early Readmissions in Decompensated Cirrhotic Patients: A Model Based on the Administrative Database

Abstract: One third of patients with decompensated cirrhosis are readmitted within 30 days of discharge. The use of simple risk scoring model with high generalizability, based on demographics, clinical features and interventions can bring refinement to the prediction of 30-day readmission in high risk patients. Mumtaz readmission risk score highlights the need for targeted interventions in order to decrease rates of readmission within this population. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
4
22
1
Order By: Relevance
“…Tapper et al used a nationwide database to report 13% and 21% readmission rates at 30 and 90 days respectively. In a recent study by Mumtaz et al, using the NRD in 2013, the authors reported higher readmission rates (27% at 30 days) compared to our findings. The higher rate observed in the Mumtaz study may be attributed to their using non‐validated ICD‐9 codes, which could overestimate cirrhosis cases .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Tapper et al used a nationwide database to report 13% and 21% readmission rates at 30 and 90 days respectively. In a recent study by Mumtaz et al, using the NRD in 2013, the authors reported higher readmission rates (27% at 30 days) compared to our findings. The higher rate observed in the Mumtaz study may be attributed to their using non‐validated ICD‐9 codes, which could overestimate cirrhosis cases .…”
Section: Discussioncontrasting
confidence: 62%
“…Unfortunately, previous studies that assessed readmission rates had significant limitations, including being driven from tertiary care centre populations, not identifying predictors of readmissions unique for each decompensated feature, not using validated cirrhosis codes and/or not assessing the economic burden on the healthcare system . As such, we used the largest nationwide readmission database in the United States to estimate hospital readmission rates and evaluate the hospitalization costs among patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Readmission risk score may highlight the need for targeted interventions to decrease rates of readmission within high-risk populations. (16) However, some factors are not easily manageable due to their complexity such as culture, socioeconomic status, and health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…These admissions and readmissions in cirrhosis are prevalent and are a major cause of healthcare expenditure . However, prediction models using clinical biomarkers alone are largely suboptimal, with relatively low c‐statistics in population‐based and cohort studies . Therefore, despite mandates to reduce hospitalisations, readmissions and early post‐discharge follow‐up efforts, these efforts are often hampered by the lack of definition of the group at greatest risk …”
Section: Introductionmentioning
confidence: 99%
“…1,2,[4][5][6] However, prediction models using clinical biomarkers alone are largely suboptimal, with relatively low c-statistics in population-based and cohort studies. 7,8 Therefore, despite mandates to reduce hospitalisations, readmissions and early post-discharge follow-up efforts, these efforts are often hampered by the lack of definition of the group at greatest risk. 7,9 Cirrhosis is associated with altered gut microbiota composition and function, which can affect the development and propagation of several complications such as hepatic encephalopathy (HE), infections such as spontaneous bacterial peritonitis (SBP) and renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%